Characterization of Hearing Thresholds from 500 to 16,000 Hz in Dentists: A Comparative Study - Gonçalves, Claudia Giglio de Oliveira; Santos, Luciana; Lobato, Diolen; Ribas, Angela; Lacerda, Adriana Bender Moreira; Marques, Jair (International Archives of Otorhinolaryngology, 2015)
Introduction High-level noise exposure in dentists' workplaces may cause damages to the auditory systems. High-frequency audiometry is an important tool in the investigation in the early diagnosis of hearing loss.Objectives To analyze the auditory thresholds at frequencies from 500 to 16,000 Hz of dentists in the city of Curitiba.Methods This historic cohort study retrospectively tested hearing thresholds from 500 to 16,000 Hz with a group of dentists from Curitiba, in the state of Paraná, Brazil. Eighty subjects participated in the study, separated into a dentist group and a control group, with the same age range and gender across groups but with no history of occupational exposure to high levels of sound pressure in the control group. Subjects were tested with conventional audiometry and high-frequency audiometry and answered a questionnaire about exposure to noise.Results Results showed that 81% of dentists did not receive any information regarding noise at university; 6 (15%) dentists had sensorineural hearing impairment; significant differences were observed between the groups only at frequencies of 500 Hz and 1,000, 6,000 and 8,000 Hz in the right ear. There was no significant difference between the groups after analysis of mean hearing thresholds of high frequencies with the average hearing thresholds in conventional frequencies; subjects who had been working as dentists for longer than 10 years had worse tonal hearing thresholds at high frequencies.Conclusions In this study, we observed that dentists are at risk for the development of sensorineural hearing loss especially after 10 years of service.
Keywords: noise induced; dentist; hearing loss